2019
DOI: 10.2196/11114
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Automated Mobile Text Messaging Reminders for Follow-Up of Positive Fecal Occult Blood Tests: Randomized Controlled Trial

Abstract: Background Fecal occult blood tests (FOBTs) are recommended by the US Preventive Services Task Force as a screening method for colorectal cancer (CRC), but they are only effective if positive results are followed by colonoscopy. Surprisingly, a large proportion of patients with a positive result do not follow this recommendation. Objective The objective of this study was to examine the effectiveness of text messaging (short message service, SMS) in increasing adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…It is essential to ensure that patients who are provided with a FIT understand the purpose of the test and what they need to do if the result is positive in advance. Reminders after completion of the test have differing degrees of effectiveness, although we found, in a previous study that telephone text reminders can increase follow-up in our population [9]. If patients are aware of the implications of non-adherence, reminders may prove to be more effective.…”
Section: Recommendationsmentioning
confidence: 51%
See 1 more Smart Citation
“…It is essential to ensure that patients who are provided with a FIT understand the purpose of the test and what they need to do if the result is positive in advance. Reminders after completion of the test have differing degrees of effectiveness, although we found, in a previous study that telephone text reminders can increase follow-up in our population [9]. If patients are aware of the implications of non-adherence, reminders may prove to be more effective.…”
Section: Recommendationsmentioning
confidence: 51%
“…Recommended strategies for early detection for population screening are either fecal occult blood testing (FOBT) yearly or colonoscopy every 10 years from the age of 50 to 74 years [2]. National CRC screening programs are available in many countries (Canada, Britain, France, Italy, Australia, Israel, Sweden and Denmark), and participation rates vary between 30 and 60%, although specific interventions have led to participation rates of up to 80% [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…36 Regarding systemrelated factors, there is evidence that systemic interventions can have moderate effects on improving uptake and adherence to FOBT testing, and can lead to increased performance of follow-up colonoscopy. 37 Furthermore, patient-level interventions which have been found to be successful in reducing waiting times after FOBT include cellphone reminders 36 and patient navigators, while reporting performance or sending reminders are effective provider-level interventions. 38 Our finding, noted by others, that increased contact with the healthcare system, as measured by the frequency of physician visits, 22,39 was related to longitudinal adherence to screening reinforces the role of health professionals in enhancing screening uptake and consistency.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, this study stemmed from a previous study 31 that examined the effect of a text message on adherence to follow-up. Therefore, participants in the current study had been randomized into an intervention group, who received an SMS alert regarding their test results, and a control group, who did not.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of follow-up colonoscopy after a positive FIT in Meuhedet was 41%. In order to improve follow-up rates, we conducted a study 31 in 2016 assessing the usefulness of sending a short message service (SMS) regarding colonoscopy follow-up after a positive FIT. We found that 17% of patients who had completed an FOBT did not remember having the test and were not aware of the test results.…”
Section: Introductionmentioning
confidence: 99%